1996
DOI: 10.1515/cclm.1996.34.9.701
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Lipoprotein Lipids in Hepatobiliary Diseases

Abstract: Summary: Liver damage and alterations in the exocrine function of the gland lead to a profound alteration of the plasma lipoprotein profile. To determine whether hepatic disease results in changes in the lipoprotein fatty acid composition, i. e. to determine whether liver function influences the homeostasis of complex lipids in plasma, we studied the fatty acid profile of lipids from VLDL, LDL and HDL, as well as from total plasma, in thirty-one patients of both sexes with hepatobiliary pathology (compensated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…In addition, ARRANZ et al [28] found that when the FA profile changes, the CE fraction is more sensitive to that change than the PL fraction. Besides, analysis of the FA composition of triacylglycerols is valid only after a strict 12-h fast because of the rapid exchange of lipids between the intestinal and the circulatory systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ARRANZ et al [28] found that when the FA profile changes, the CE fraction is more sensitive to that change than the PL fraction. Besides, analysis of the FA composition of triacylglycerols is valid only after a strict 12-h fast because of the rapid exchange of lipids between the intestinal and the circulatory systems.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic injury leads to changes in serum lipids, lipoprotein, cholesterol, triglycerides, and some related enzymatic activities (23). In addition, hepatic injury can be influenced by changes in polyunsaturated fatty acids (24).…”
Section: Discussionmentioning
confidence: 99%
“…Being the smallest lipoproteins, HDL are secreted by the liver and intestine and transport cholesterol back to the liver 78 . Low HDL cholesterol levels are seen in human patients with liver diseases such as acute viral hepatitis and severe cholestasis 79 , as well as liver cirrhosis, and can arise from multiple causes 80 82 . Lower HDL cholesterol concentrations were also associated with decreased survival time in patients with liver cirrhosis and acute gastrointestinal bleeding 81 and also predicted the development of complications associated with liver cirrhosis 82 .…”
Section: Discussionmentioning
confidence: 99%